ANALISIS KELAYAKAN FINANSIAL USAHA PERKEBUNAN KARET POLA SWADAYA DI DESA PULAU JAMBU KECAMATAN KUOK KABUPATEN KAMPAR - Siti Azizah; Suardi Tarumun; Yusmini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Rubber (Hevea brasiliensis) is one of the most important cash crops cultivated by the people In Riau Province. This objective of this research is to analyze financial feasibility of rubber plantation in Pulau Jambu Village Kuok district Kampar Regency, Riau. Primary data used in this research were obtained thorugh direct interviewes with farmers, middle men and whole sellers which include prices of rubber, fertilizer, labor, land values and other inputs. Secondary data was obtained from government and other relevant agencies. To analyze data we use investment criteria namely, NPV (Net Present Value), IRR (Internal Rate of Return), Net B/C (Net Benefit Cost Ratio) and sensitivity analysis. The results showed the value of NPV, Net B/C and IRR are Rp 298,163,463, 2.46 and 26.12% subsequently. The average income of rubber farmers is Rp 993,878 per month. Sensitivity analysis of this research is also done in three aspects: the 5% changes of production level, 40% change of output prices and 10% changes of input prices. The results of these three simulations show that value of NPV decrease only about 2.24%, 47.96% and 1.90% subsequently, while IRR is greater than the discount factor of 12% and the value of Net B/C > 1. Weconclude that the rubber plantation cultivation still worthy because it still able to provide the level of welfare for self-rubber farmers in Pulau Jambu Village, Kuok distict . Keywords: Rubber, NPV, IRR, Net B/C, Sensitivity Analysis.